Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3892/mmr.2014.1971
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of chlorhexidine and essential oils containing mouth rinse on stem cells cultured on a titanium surface

Abstract: Chlorhexidine (CHX) and Listerine (LIS), an essential oil compound, are the two commonly used adjunctive agents for mechanical debridement, for reducing the bacterial load in the treatment of peri-implant inflammation. However, antimicrobial agents have been reported to be cytotoxic to the alveolar bone cells and gingival epithelial cells. The present study was performed to examine the effects of antiseptics CHX and LIS, on the morphology and proliferation of stem cells. Stem cells derived from the buccal fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Undiluted Listerine® induced near‐complete cell death 24 h after a 60‐s treatment of human gingival and periodontal ligament fibroblasts (Tsourounakis et al , ). Likewise, a 30‐s treatment of stem cells derived from a buccal fat pad and grown on machined titanium disks showed a reduction in cellular viability (Park et al , ). On A‐375 cells, M exerted in vitro cytotoxic effects, with an IC 50 value of 0.012 mM (the M concentration in Listerine® is 2.69 mM) (Kijpornyongpan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Undiluted Listerine® induced near‐complete cell death 24 h after a 60‐s treatment of human gingival and periodontal ligament fibroblasts (Tsourounakis et al , ). Likewise, a 30‐s treatment of stem cells derived from a buccal fat pad and grown on machined titanium disks showed a reduction in cellular viability (Park et al , ). On A‐375 cells, M exerted in vitro cytotoxic effects, with an IC 50 value of 0.012 mM (the M concentration in Listerine® is 2.69 mM) (Kijpornyongpan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils were found to decrease biofilm activity and biomass [134,135]. It was also reported to be antifungal and inhibitory to the adherence of C. albicans onto dental implants and cover screws in vitro [135], with commented that the essential oils were capable of promoting penetration to the deep structure of biofilm and destroy more pathogenic resistant forms.…”
Section: Essential Oilsmentioning
confidence: 96%
“…This reduction in cellular viability was observed even after 30 s of exposure. Park et al (2014) suggested that further studies should attempt to ascertain more exactly the optimal therapeutic range (frequency, duration, and concentration) for these rinses. That might at least minimize the cytotoxicity to the surrounding cells without reducing the usefulness of the products.…”
Section: Safety Of Listerine®mentioning
confidence: 99%